Pembangunan Rumah Tinggal dengan Sistim Arisan di Desa Pangan Jaya - Muhammad Zakaria Umar (EMARA: Indonesian Journal of Architecture, 2017)
The effort to find national identity based on local wisdom became important. One of the local wisdom that can be found in Pangan Jaya villages is Arisan system in building the villager houses. The village of Pangan Jaya were inhabited by former transmigration communities from Lamongan and Bojonegoro districts in East Java Province. Soon as their arrival at transmigration area called Pamandati, those peoples experienced difficulties in daily life. The condition creates a sense of togetherness spontaneously, because their mutual sense in cultivated the farmland. They embody solidarity and mutual assistance (gotong royong) in the form of Arisan that represents their homelands culture. They felt the mutual cooperation habit that they have done in their homeland need to be applied in their new village even though they did not know each other before. The houses built by Pangan Jaya peoples were the result of mutual cooperation in the form of Arisan. The research aimed to study the form of Arisan system among the people of Pangan Jaya village in building their houses. This was a qualitative study with case study approach and data were collected through observation as well as in-depth interviews. The result of the research indicated that the Arisan system on houses construction came in the form of building materials and cash money. This Arisan system can run well because of the similarity of background, life principle and Javanese culture among Pangan Jaya villagers and supported by their healthy economy condition.